Oral Health and Aging - Hogue, Christie-Michele.; Ruiz, Jorge G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides a comprehensive review of the assessment and management of older people$1 (Bs oral health care needs. Discussing recent initiatives to emphasize oral health promotion and prevention, the book describes improvements in pharmacological and non-pharmacological approaches for special populations in geriatrics and illuminates the role of barriers to oral health care for older people. Divided into three sections, the book first explores aging and oral health, including age-related changes, epidemiology, nutrition, dysphagia, aspiration pneumonia, xerostomia and hyposalivation, management of periodontal disease and caries, systemic diseases that influence oral health, and considerations for chronic orofacial pain. The second section illuminates the ways in which frailty and other geriatric syndromes influence oral health care in older adults with a special focus on frailty, dementia, delirium and depression, and the delivery of oral health care to vulnerable geriatric populations in long-term care, home care, palliative care, and hospice. Lastly, the book addresses inequalities in the oral health of older minority populations, the disproportionate burden of oral disease and tooth loss, the contribution of these issues to further complications in comorbidities, the association of extended health literacy and periodontal disease, and the social and cultural conditions that might be altered or improved by healthcare programs and health policies. Oral Health and Aging is a useful book written by an international group of experts and designed to educate geriatricians, primary care physicians, nurses, dentists, dental hygienists, speech and language pathologists, dietitians, and health policy advocates.s
Age-Related Changes in Oral Health -- Epidemiology of Oral Conditions in Older Populations -- Nutrition and Oral Health in Older Adults -- Swallowing, Dysphagia, and Aspiration Pneumonia -- Xerostomia and Hyposalivation in Older Adults -- Management of Periodontal Disease in Older Adults -- Caries Management and Restorative Dentistry in Older Adults -- Systemic Disease that Influences Oral Health -- Oral Health and the 3 Ds: Dementia, Delirium and Depression -- Oral Care in Long Term Care Settings -- Oral Health Care for Patients Receiving Palliative Care or Hospice -- Ethical Considerations in Geriatric Dentistry -- Health Disparities and Older Adults -- Physical Frailty and Oral Health -- The Role of Oral Health Literacy in Shared Decision Making -- Barriers to Accessing Dental Care for Older Adults.
Keywords: Geriatrics; Geriatrics; Oral Health; Aged; Dental Care for Aged; Geriatric Dentistry